The complete chloroplast genome of an endemic plant to Korea, Cardamine amaraeformis Nakai.: genome structure and phylogenetic analysis - Gurusamy Raman; Kyu Tae Park; SeonJoo Park (Mitochondrial DNA. Part B. Resources, 2021)
The plant Cardamine amaraeformis Nakai. is considered an endemic plant to Korea. However, due to the similar morphological characteristics of C. amaraeformis with C. scutata, it is not easy to distinguish these two species. Here, the complete chloroplast genome of C. amaraeformis was sequenced and characterized. The chloroplast genome of C. amaraeformis was 155,598 bp in length, comprising a large single-copy (LSC) region of 84,574 bp and a small single-copy (SSC) region of 17,976 bp and a pair of inverted repeats (IRs) of 26,524 bp. The genome contained 131 genes, including 86 protein-coding (PCGs), 37 tRNA and 8 rRNA genes. Of those, 6 PCGs, 8 tRNA and 4 rRNA genes were duplicated in the IR region and one gene was a pseudogene. The GC content of the C. amaraeformis chloroplast genome was 36.3%. Phylogenetic analysis revealed that all Cardamine species formed a monophyletic clade and C. amaraeformis was closely associated with C. parviflora. Therefore, the present study could help to distinguish C. scutata and resolve the phylogenetic relationships among the Cardamine lineage.